FoodPrice: Un paquete en R para la estimación de dietas de costo mínimo - González, Daniel; Barona, Sergio A.; Ordoñez, Juan Camilo (2024)
This package provides tools to estimate the minimum cost of a diet that meets the following criteria: sufficiency in energy, adequacy in nutrients, and health promotion. Developed in collaboration with Pontificia Universidad Javeriana Cali and the Alliance Bioversity-CIAT, the package offers functionalities that allow calculating and optimizing the cost associated with the preparation of healthy and balanced diets.